Spacecraft observations of energetic neutral atoms - Ovaskainen, Anssi (My University, 2018)
The use of Energetic Neutral Atom (ENA) observations to remotely and globally survey populations of plasma in the context of space physics is examined. General characteristics of ENAs and the methods of their detection are covered, as well as three science cases that act as examples of the use of the technique. For sake of brevity, the coverage of the subject is mostly limited to detections of ENAs that have energies of 1 keV or more. The first three chapters are in the form of a literature review. The fourth chapter utilises previously published data to estimate ENA fluxes from the terrestrial ring current in Low Earth Orbit at energies exceeding 100 keV. This is done to examine the possibility of observing ENAs related to solar eruptions with a detector mounted to a micro-satellite. The main advantage of ENA detections is their global nature. It would not have been possible to obtain the results shown in chapter 3 with more traditional in situ-observations of ions. ENA observations can be used to gain new insights into known systems and they open possibilities of discovering new phenomena. On the other hand, work is still under way to mitigate the technical limitations related to instrument sensitivity and available angular resolutions. While the observation technique is still under development, the concept has been proven to be sound many times over.
Keywords: Energetic neutral atoms, ENA imaging, Space instrumentation, Heliosphere, Ring current